Comparative study of leaf anatomy of Malaysian species of Chionanthus and Olea (Oleaceae) with special reference to foliar sclereids - Kiew, Ruth; Ibrahim, Che Su (Linnean Society of London, 1982)
The foliar anatomy of 15 Malaysian species of Chionanthus and 3 species of Olea is described and compared with particular reference to sclereids. The anatomy of the two genera is similar except that Chionanthus shows a wider range in sclereid form, eight kinds ofsclereid are recorded. Filiform sclereids are present in all Olea species and most Chionanthus species examined, additional kinds ofsclereid found in these Chionanthus species include astrosclereids, dendrosclereids, osteosclereids and polymorphic sclereids, with brachysclereids of several forms in the petiole. Quantity of sclereids is not related to coriaceousness, which is determined by leaf thickness. Anatomical characters do not support any major grouping of species within Chionanthus and provide further evidence that the sections, Eulinocitra and Ceranthus, are untenable. The distinction between the lepidote scales of Olea and the peltate hairs common to all oleaceous genera is discussed.